The Effect of Some Herbal Extracts on Nitric Oxide Production in Endothelial Cells 3T3 Cell Line: The Effect of Some Herbal Extracts on Nitric Oxide Production - Reza Mohebbati,; Farimah Beheshti,; Mozhdeh Iranmanesh,; Mina Rohani,; Mojtaba Mousavi,; Marzieh Mogharrabi,; Mohammad Soukhtanloo, (Iranian Journal of Pharmaceutical Sciences, 2016)
Some studies have demonstrated the potential of herbal drugs for the treatment of various diseases associated with impaired vascular nitric oxide (NO). For diagnosis of the mechanism of these herbal plants, it seems necessary to evaluate the herbal extracts on the Endothelium cell. The aim of the study was to investigate the effect of extract of Trigonella foenum-graecum (T.foenum), Nigella sativa (NS), Allium sativum, and Cannabis sativa on nitric oxide (NO) production by the endothelial cells 3T3 cell line.Ground herbs suspended in water and methanol, were filtered and concentrated under pressure. Remaining contents were dried and obtained powder dissolved in water. The cell line was treated with plant extracts. The clarified supernatant of the culture was used for evaluation of quantitative changes in NO production using Griess test.Among the four extracts, only the group treated with T.foenum extract, significantly increased NO production compared to the control group. Also, NO concentration in other extract group was lower than T.foenum group. This study suggested that the T.foenum extract can significantly increase NO concentration in cell culture and the increase in nitric oxide production is because of the presence of diosgenin T.foenum extracted.